The Relative Citation Ratio: Evaluating a New Measure of Scientific Influence Among Academic Sports Medicine Surgeons. Issue 1 (20th January 2023) - Smith, Tiffany A.; Sudah, Suleiman Y.; Manzi, Joseph E.; Michel, Christopher R.; Kerrigan, Daniel J.; Dijanic, Christopher N.; Constantinescu, David S.; Menendez, Mariano E.; Plyler, Ryan
Background: Objective measures of research influence are being increasingly utilized to evaluate and compare academic faculty. However, traditional bibliometrics, such as the Hirsch index and article citation count, are biased by time-dependent factors and are limited by a lack of field normalization. The relative citation ratio (RCR) is a new field- and time-normalized article-level metric developed by the National Institutes of Health (NIH). Purpose/Hypothesis: The purpose of this study was to evaluate the RCR among fellowship-trained academic sports medicine surgeons and to analyze physician factors associated with RCR values. We hypothesized that the mean RCR score for fellowship-trained academic sports medicine surgery faculty will fall above the NIH standard. Study Design: Cross-sectional study. Methods: A retrospective data analysis was performed using the iCite database for all fellowship-trained sports medicine surgery faculty associated with Accreditation Council for Graduate Medical Education–accredited orthopaedic surgery residency programs in December 2021. In eligible faculty, the mean RCR, weighted RCR, and total publication count were compared by sex, career duration, academic rank, and presence of additional degrees. A mean RCR value of 1.0 is the NIH-funded field-normalized standard. The data herein are presented as the median and interquartile range, in addition to the mean and standard deviation, to account for outliers of the mean and weighted RCR scores. Results: A total of 624 fellowship-trained sports medicine surgery faculty members from 160 orthopaedic surgery residency programs were included in the analysis. Overall, faculty produced impactful research, with a median RCR of 1.6 (interquartile range, 1.0-2.2) and a median weighted RCR of 19.3 (interquartile range, 5.1-69.3). Advanced academic rank and career longevity were associated with increased weighted RCR and total publication count. All subgroups analyzed had an RCR value >1.0. Conclusion: Study findings indicate that fellowship-trained academic sports medicine surgery faculty are highly productive and produce impactful research, as evidenced by the high median RCR value relative to the benchmark NIH RCR value of 1.0.